2015
DOI: 10.1021/acsami.5b08817
|View full text |Cite
|
Sign up to set email alerts
|

Nanoprobe-Initiated Enzymatic Polymerization for Highly Sensitive Electrochemical DNA Detection

Abstract: Electrochemical DNA (E-DNA) sensors have been greatly developed and play an important role in early diagnosis of different diseases. To determine the extremely low abundance of DNA biomarkers in clinical samples, scientists are making unremitting efforts toward achieving highly sensitive and selective E-DNA sensors. Here, a novel E-DNA sensor was developed taking advantage of the signal amplification efficiency of nanoprobe-initiated enzymatic polymerization (NIEP). In the NIEP based E-DNA sensor, the capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…图 17 基于OTA适配体和TDT介导超长聚胸腺嘧啶转换的 Cu NPs的OTA荧光测定示意图 [49] (网络版彩图) 图 19 基于近端双向酶修复扩增的ATP荧光检测原理图 [51] (网络版彩图) 图 18 末端脱氧核苷酸转移酶(TdT)辅助扩增策略在黄瓜 绿斑驳花叶病毒视觉检测中的应用原理图 [50] (网络版彩图) [46] (网 络版彩图) 图 21 基于NIEP的E-DNA生物传感原理 [52] (网络版彩图)…”
Section: 酶解交联水凝胶unclassified
“…图 17 基于OTA适配体和TDT介导超长聚胸腺嘧啶转换的 Cu NPs的OTA荧光测定示意图 [49] (网络版彩图) 图 19 基于近端双向酶修复扩增的ATP荧光检测原理图 [51] (网络版彩图) 图 18 末端脱氧核苷酸转移酶(TdT)辅助扩增策略在黄瓜 绿斑驳花叶病毒视觉检测中的应用原理图 [50] (网络版彩图) [46] (网 络版彩图) 图 21 基于NIEP的E-DNA生物传感原理 [52] (网络版彩图)…”
Section: 酶解交联水凝胶unclassified
“…Furthermore, due to AuNPs’ wide specific surface area, they can be filled with a high number of labels and used for amplified detection of nucleic acids. Indeed, AuNPs have been functionalized with unlabeled [13] or redox-labeled [14] nucleic acid probes, redox molecules [15,16], and enzymes or DNAzymes.…”
Section: Aunps Aunws Janus and Magnetic Nanoparticles: Synthesismentioning
confidence: 99%
“…Attractive strategies for the sensitive electrochemical detection of nucleic acids have also been proposed using AuNPs as nanocarriers of redox-labeled DNA probes [14,15], DNA probes and enzymes [13], and redox reporters [15,16]. Wang et al [14] reported a sandwich hybridization assay at an Au electrode modified with a thiolated capture probe and the use of AuNPs modified with two types of signaling reporter DNAs labeled with methylene blue (where just one was complementary to the target DNA).…”
Section: Biosensing and Delivery Of Nucleic Acids: Roles Opportunmentioning
confidence: 99%
See 2 more Smart Citations